Plasma fibronectin can affect the cytokine profile and monocytes/macrophages function in addition to predicting the prognosis of advanced sepsis. Issue 3 (19th February 2022) - Yuan, Xiaohong; Wu, Yong; Lin, Jia; Weng, Qinyong; Wu, Linqing; Yang, Shu; Li, Xin; Tan, Ming; Lin, Zhenxing; Lian, Xiaolan; Chen, Yuanzhong
Abstract: The value of plasma fibronectin (pFN) in the diagnosis and prognosis of sepsis has not been fully established. Previous studies finding that pFN is significantly reduced in sepsis, however, whether reduced pFn affects the prognosis of sepsis has not been clarified. Here, we detected and analyzed pFN and other conventional inflammatory markers in advanced sepsis patients and performed correlation analysis with SOFA score. We also used Fn gene conditional knockout mice which were performed by cecum ligation and puncture (CLP) to investigate the effect of FN deficiency on sepsis prognosis. We found, compared with procalcitonin, c‐reactive protein, and interleukin‐6, pFN was more correlated with SOFA score in advanced sepsis patients ( r −.720, p  < .001). In animal experiments, Fn gene knockout mice showed significantly greater mortality after CLP compared with the control group because of inhibited phagocytosis and bacterial clearance ability of macrophages, with double cytokine storm. Furthermore, FN can regulate macrophages through the integrin α5β1/Fak/Src signaling pathway. Overall, we found pFN can more accurately reflect the severity and prognosis of advanced sepsis. The absence of FN altered the cytokine storm and phagocytic function of macrophages, suggesting that FN could be a potential therapeutic target in sepsis.